THE ROLE OF ISLAMIC BOARDING SCHOOLS IN THE ECONOMIC EMPOWERMENT OF STUDENTS (Case Study at Sunan Drajat Paciran Lamongan Islamic Boarding School) - Fatah, Abdul; Syamhadi, Syamhadi; Sofiyatun Nurih, Nining; Qoyyimah, Hofifatul; Sari Dewi, Riskawati (At-Turost : Journal of Islamic Studies, 2022)
Islamic boarding school of Sunan Drajat Paciran Lamongan is one of the boarding schools that have successfully developed an economic program that aims to empower the students. Sunan Drajat boarding school aims to transform the social life of society, both the education, da'wah of Islam and social. In the economic context, boarding school has successfully applied economic concepts that tend to be mu'amalah be iqtishadiyyah (economic) application concept. This study aims to determine the role of boarding school Sunan Drajat in the economic empowerment of students (santri). This research uses qualitative approach with case study model. While the method used is explanative explaining how the role of boarding school Sunan Drajat in conducting economic empowerment of students. Methods of data collection used, among others, by observation, interview and documentation. Interviews were conducted in three categories: chiefs of Islamic boarding, students(santri), and community. The results of this study indicate that the role of boarding school Sunan Drajat in an effort to empower students (santri) divided into two namely; empowerment through education and empowerment through skills and entrepreneurship training